2020
DOI: 10.1111/ppa.13289
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year survey uncovers extensive diversity and temporal fluctuations among fusarium head blight pathogens of wheat and barley in Brazil

Abstract: We conducted a five‐year survey (2011–2015) of barley and wheat fields in Paraná state, Brazil, obtaining 754 Fusarium isolates from spikes with fusarium head blight (FHB)‐symptoms. Multilocus genotyping and TEF‐1α gene sequence analyses confirmed the dominance of the F. graminearum species complex (FGSC, 75.7%), but F. poae (11.5%), as well as F. avenaceum and related members of the F. tricinctum species complex (FTSC, 8.1%) appeared as substantial contributors to FHB. Within the FGSC, F. graminearum of the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 62 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…Higher FGSC species diversity was found in wheat crops grown at lower latitudes, near to or within subtropical environments (Pereira et al 2021;Umpiérrez-Failache et al 2013). This suggests that there is also an effect of climate in shaping species distributions, as posited previously by a modelling study (Backhouse 2014).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Higher FGSC species diversity was found in wheat crops grown at lower latitudes, near to or within subtropical environments (Pereira et al 2021;Umpiérrez-Failache et al 2013). This suggests that there is also an effect of climate in shaping species distributions, as posited previously by a modelling study (Backhouse 2014).…”
Section: Discussionsupporting
confidence: 70%
“…In wheat and barley, members of the FGSC cause Fusarium Head Blight (FHB), which re-emerged as a major concern throughout the world in the early 1990s (Goswami and Kistler 2004;McMullen et al 1997McMullen et al , 2012. Numerous surveys of disease incidence and severity, pathogen population diversity, and mycotoxin contamination have been conducted during the past three decades in the main cereal-growing regions of the world where FHB epidemics have occurred (Cowger et al 2019;Pereira et al 2021; van der Lee et al 2015;Vogelgsang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work where F. acuminatum 33T was cultivated on FDM-agar medium, its level of ENNs’ production was 10-fold higher than for a strain of F. avenaceum cultivated under the same conditions [ 14 ]. Comparing the single F. acuminatum strain with 30 F. avenaceum they isolated in a survey of barley and wheat fields in Paraná state, Brazil, Peirera et al [ 41 ] found F. acuminatum to be the strongest producer of ENNs. Despite its low occurrence, F acuminatum has to be considered as a significant source of mycotoxin contamination of crops, due to its high potential for ENNs’ production.…”
Section: Discussionmentioning
confidence: 99%
“…However, the growth of filamentous fungi in barley is a concern for the food industry and it mainly happens due to inappropriate management during the pre-harvest, transportation, and storage of cereal grains [ 27 ]. In addition, climatic conditions associated with insect infestation and intrinsic factors of the raw material are considered relevant, as they may favor the development of these microorganisms and mycotoxin production, which are toxic secondary metabolites mainly produced by the genera Alternaria , Aspergillus , Fusarium , and Penicillium , with the Fusarium graminearum species complex (FGSC) often reported in barley (dominant species, with more than 80% frequency) [ 28 , 29 , 30 ]. Another species that is important to study is F. meridionale , which significantly contributes to the Fusarium Head Blight (FHB) disease of wheat in Paraná and Rio Grande do Sul, Brazil.…”
Section: Introductionmentioning
confidence: 99%